Resource Recovery from Synthetic Nitrified Urine in the Hydroponic Cultivation of Lettuce (Lactuca sativa Var. capitata L.) - Anna Jurga (MDPI AG, 2021)
The application of hydroponic cultivation fertilized with biologically nitrified synthetic urine can produce nitrate-rich fertilizer for lettuce (Lactuca sativa var. capitata L.). The mounting water crisis and depletion of natural resources makes nitrogen recovery from human urine a practical option. Nitrified urine can be used in indoor vertical hydroponic cultivation and is characterized by a high degree of element recovery. Because of its high ammonium content, hydrolyzed fresh urine may be toxic. A nitrification sequencing batch reactor with suspended activated sludge biomass ensured urine stabilization and biological conversion into nitrate-rich fertilizer. The diluted nitrate-rich fertilizer was then supplied for soilless cultivation. The results show that diluted nitrified urine is an excellent source of bioavailable nitrogen and phosphorus and, with proper enrichment with microelements, could replace commercial fertilizers in hydroponic systems. The yield and quality parameters of lettuce cultivated with enriched urine were comparable to those obtained with a commercial fertilizer. The mass balance calculation showed that industry-scale lettuce production can be based on urine fertilizer collected from a few hundred people for a single unit.